Solaris 9 : - Docter, Quentin (Sybex, 2003)
With over a million licensed users for Solaris 8, Sun Microsystems successfully launched the long awaited Solaris 9 O/S in May 2002. Soon after, Sun revamped their popular certification track to include two tiered certifications. With new objectives, the Certified System Administrator, is positioned to be one of the most popular IT certifications. In order to obtain your Certified System Administrator certification, one must pass two exams. Note: CD-ROM/DVD and other supplementary materials are not included as part of eBook file.